Penetrant-induced plasticization in glassy polymer membranes for gas separation - Wong, Lorna; Ismail, Ahmad Fauzi (2000)
The present paper deals with the performance of glassy polymer membranes plasticized by penetrant gases. Penetrant induced plasticization of gas separation membranes has been the subject of a number of recent investigations. Historically, plasticization can be attributed to the swelling stresses exerted by the penetrant molecules on the polymer network. It appears that carbon dioxide behaves as a plasticizing agent for many glassy polymers by expandng the polymer lattice and increasing the frequency of molecular motions. In glassy polymers, the permeability to carbon dioxide is pressure dependent. Permeability can either increase or decrease with increasing feed pressure.It was thought that the permeability of most glassy polymers to gases decreases with increasing pressure in accordance with the predictions of the dual-sorption theory. Presumably, the plasticizing action of CO2 decreases the ability of the membrane to separate molecules thereby causing the reduction in selectivity. In gas separation membranes, plasticization effects are observed as anomalous sorption and permeation during measurements at elevated pressures. The alteration of a number of properties resulting from the polymer conditioning by the sorbed penetrant molecules was investigated. It has been demonstrated that high sorption of carbon dioxide results in a strong plasticizing effect on the properties of several polymers. Disentanglement of polymer chains at elevated pressure, the depression of the glass transition temperature by absorbed CO2 molecules, the decreasing of activation energy for diffusion with increasing concentration visualize the plasticization effect of carbon dioxide on glassy polymers.